The Hobbesian psychology of the US firearms debate. Issue 3 (2nd July 2020) - Reed, Ryan; Hallenbrook, Christopher R.
ABSTRACT: In the US, headlines announcing firearm casualties have become routine. In response, the loudest and most efficacious voice among gun rights lobbyists, the NRA, consistently insists that more firearms in the hands of more people is the solution to the violence. Such a notion bears a striking resemblance to the Hobbesian conception of the state of nature, wherein no common authority exists to keep the peace. Leading from that inspiration, this paper analyzes the Hobbesian psychology of the gun violence predicament in which the United States finds itself. We argue that looser gun restrictions and increased gun possession advocated by gun rights activists – and largely being adopted across vast swaths of the US – do not follow from the underlying Hobbesian assumptions of their arguments. Further, their stance represents an attempt to carry unfettered natural right into the commonwealth, which portends the termination of the commonwealth itself.